α-substituted bis(octabutoxyphthalocyaninato)Terbium(III) double-decker complexes: preparation and study of protonation by NMR and DFT - Damjanović, Marko; Horie, Yusuke; Morita, Takaumi; Horii, Yoji; Katoh, Keiichi; Yamashita, Masahiro; Enders, Markus (Inorganic chemistry, 2015)
Synthesis of the anionic, α-substituted, bis(phthalocyaninato)TbIII complex [Tb(α-obPc)2]— ([1]—) (obPc = α-octabutoxyphthalocyaninato) leads to the isolation of its protonated form [1H]0. This complex was characterized by X-ray diffraction (XRD), mass spectroscopy (MS), infrared (IR) and ultraviolet-visible-near-infrared (UV-vis-NIR) spectroscopy. Crystal structure analysis did not allow localization of the additional proton, which is probably attached to the meso-N atom or isoindole-N atom of the phthalocyaninato ligand. [1H]0 can easily be deprotonated or protonated, giving the corresponding anionic and cationic complexes. The three compounds [1H]0, [1]—, and [1HH]+ were studied by a combination of paramagnetic NMR experiments (1H, 13C, variable-temperature measurements, two-dimensional nuclear magnetic resonance and DFT calculations (done on YIII analogues with octamethoxyphthalocyaninato ligands), for the purpose of elucidating the positions of the acidic protons and for understanding the structural changes of the coordination environment of the Tb ion induced by protonation.
Gesehen am 18.01.2021